Risk factors for the progression of distal adding-on phenomenon after surgery in patients with Lenke type 1 and 2 adolescent idiopathic scoliosis - Tao Li; Yong Li; Xiangbin Wang; Yubin Long (Scientific Reports)
Abstract To investigate risk factors associated with the progression of the distal adding-on phenomenon after posterior selective thoracic fusion in patients with Lenke type 1 and 2 adolescent idiopathic scoliosis (AIS). A retrospective analysis was conducted on 152 patients who underwent posterior selective thoracic fusion from December 2015 to December 2021. Among them, 48 patients experienced the distal adding-on phenomenon postoperatively. Based on whether this phenomenon progressed during follow-up, they were divided into progressive and non-progressive groups. Univariate analysis compared clinical and imaging data between the two groups, while multivariate logistic regression identified independent risk factors. Of the 48 patients with postoperative distal adding-on, 37 (77.1%) were non-progressive and 11 (22.9%) were progressive. Univariate analysis showed significant differences between the progressive and non-progressive groups in Risser sign grade (2.27 ± 1.10 vs. 3.73 ± 0.87, P < 0.001), number of segments between lowest instrumented vertebra (LIV) and the last substantially touched vertebra (LSTV) (-1.27 ± 0.79 vs. 0.51 ± 1.17, P < 0.001), preoperative clavicle angle (-2.55 ± 2.84 vs. -0.11 ± 2.82, P = 0.015), and preoperative trunk shift (21.05 ± 15.27 vs. 10.46 ± 13.32, P = 0.030). Multivariate analysis confirmed that lower Risser sign grade (OR = 0.16, 95% CI 0.03–0.82, P = 0.028) and fewer segments between LIV and LSTV (OR = 0.07, 95% CI 0.01–0.58, P = 0.013) were independent risk factors for the progression of the distal adding-on phenomenon. Lower skeletal maturity (Risser sign grade) and LIV located cephalad to LSTV are independent risk factors for the progression of the distal adding-on phenomenon in patients with Lenke type 1 and 2 AIS. For skeletally immature patients (Risser ≤ 3), LSTV should be preferentially chosen as LIV during surgery.